"Living in the brothel": Participant observation in hidden contexts. Issue 3 (3rd July 2021) - Meneses-Falcón, Carmen
ABSTRACT: This article describes the difficulties of the research and application of participant observation in hidden contexts and in behaviours that are considered taboo or intimate in western societies. Ethnographic work in four brothels of female prostitution was carried out in four Spanish cities, in which the author lived with the women and employees of the brothels. Aspects that arise during the ethnographic work are reflected upon: selection of and access to the spaces of interaction, the roles to be carried out by the researcher, the limits of the participation, the legal and ethical codes, acceptance by the informants and the learning of hidden meanings. Managing to pierce hidden contexts and meanings is only possible through participant observation with very close relationships of trust with the subjects under study, which is only attainable through daily coexistence.